Study of the 32S(3He, d)33Cl one-proton transfer reaction with a new generation hodoscope. (August 2019) - Cinausero, M; Dell'Aquila, D; Lombardo, I; Vigilante, M; Barlini, S; Bolzonella, R; Bruno, M; Buccola, A; Cartuan, S; Casini, G; Cicerchia, M; D'Andrea, M; et al.
Abstract: The 32 S( 3 He, d) 33 Cl one-proton transfer reaction is a powerful tool to investigate the spectroscopy of low-lying states in the proton-rich 33 Cl nucleus. However, the extraction of firm differential cross-section data at various angles, against which benchmarking theoretical models to correctly constrain the spectroscopy of 33 Cl, is made challenging by the presence of competitive reaction products contaminating the detected energy spectra. We have recently measured the 32 S( 3 He, d) 33 Cl reaction at 9.8 MeV incident energy by using a new generation hodoscope of silicon detectors, capable to detect and identify emitted deuterons down to energies of the order of 2 MeV. The high angular segmentation of our hodoscope allowed to unambiguously disentangle the contribution of one-proton transfer reactions in the ground state of 33 Cl and in its 0.810 MeV, 2.352 MeV, 2.685 MeV, 2.846 MeV excited states from contaminant deuteron-emitting reactions. These data will be crucial to help to constrain J π and spectroscopic factor C 2 Sp values of low-lying 33 Cl states, still ambiguous in the literature. The present status of the analysis is discussed in the paper.